(NaLEATORIKA KAK PRINCIP KOMPOZICIIs (NU^EBNOE POSOBIEs - (Nm(B.(Nw(B.(NpEREWERZEWAs ((NsANKT(B-(NpETERBURGs (NlAN_s (NpLANETA MUZYKIs, 2020)
(NaLEATORIKA(B-(NMETOD KOMPOZITCII W MUZYKE hh(B-(Nhh(BI (NWEKOW(B,(NDOPUSKA@]IJ WARIA(B-(NBEL_NYE OTNO[ENIQ MEVDU \LEMENTAMI MUZYKAL_NOJ TKANI PROIZWEDENIQ(B.s
Keywords: (NmETODIKAs